Cancer Narratives in Instagram: Self-presentation of Cancer Patients - V. G. Silantieva; A. V. Kozhokina (Дискурс, 2021)
Introduction. The paper aims to establish whether cancer discourse can alter when being communicated via social networks. We supposed that every platform has intrinsic characteristics which might affect the way certain topics are being delivered. Because there has been much criticism from the cancer community about the media representation, we decided to observe what might be called an alternative discourse of cancer of social networks. Therefore, we chose to review Instagram accounts of two cancer influencers, who aspire to revise existing stereotypes about people with an incurable disease.Methodology and sources. The chosen methodology includes the statistical concordance analysis, Metaphorical Identification Procedure (MIP), structural semantic and syntactic studies of two narratives organized as a minicorpus. The combined approach was employed to reveal lexical markers of both cancer discourse and Instagram narratives in the narratives of two Insta influencers Nicky Newman and Laura Hughes.Results and discussion. The results of the study suggest that Instagram narratives of cancer patients differ from other texts about cancer. Bloggers strive to maintain constant simultaneous communication with a large number of people; therefore, their texts are designed to be entertaining, involving and diverse in subject matter. When narrating about their life with the cancer diagnosis, bloggers broadcast a positive media image of a happygo-lucky person. In the narratives chosen for this study, there is hardly an example of the CANCER-WAR metaphor. The main ways of conceptualizing cancer are the CANCERCONSPIRACY, CANCER-JOURNEY, CANCER-COHABITANT metaphors.Conclusion. Quantitative analysis of the English language corpus aimed at identifying key words and concordances of the lexeme ”cancer”, does not help fully define the cancer discourse. It is necessary to further research into the obtained data. Consequently, it is necessary to take into account the genre of ”cancer” narratives.